Perancangan Sistem Informasi Perdesaan Berbasis Android - Khairul Azmi; Dewi Mulyati; Taufik Hidayat (Design Journal, 2023)
The research objective was to design an android-based rural information system at the Montasik Aceh Besar sub-district office, as a service in rural storage and services and it is hoped that it can be used as a reference for making a faster and more accurate android-based rural information system. The method used in designing an Android-based rural information system is using the waterfall method. The design results consist of service features for the community. services for making letters, searching for population data and village information by village officials, thereby increasing the work efficiency of village officials and village administration to become more orderly and regular. The Android-based rural information system for Montasik District is software that was built to help manage website and Android-based, with correspondence making services starting from requests for Family Cards, Resident Cards, Certificates of Inability, Death Certificate, Birth Certificate, Versatile Certificate, Transfer Certificate, Marriage Certificate, Business Certificate, and Certificate of Good Conduct, as well as information about the Village (vision and mission, Profile, History, Village Potential). Thus this system can be used as a tool to support the performance of village officials as well as a media for village promotion to make Montasik District Village an icon of a tourism village, especially in the Aceh Besar District area.